Spatially-resolved photoluminescence imaging of CdS and GaAs/AlGaAs nanowires - Smith, L; Hoang, T; Titova, L; Jackson, H; Yarrison-Rice, J; Lensch, J; Lauhon, L; Kim, Y; Joyce, H; Jagadish, C (2007)
We use low temperature spatially resolved photoluminescence imaging to study optical properties and electronic states of single CdS and GaAs/AlGaAs core-shell nanowires. © 2007 American Institute of Physics.